Carry-over assessment of fumonisins and zearalenone to poultry tissues after exposure of chickens to a contaminated diet – A study implementing stable-isotope dilution assay and UHPLC-MS/MS. (January 2020) - Hort, Vincent; Nicolas, Marina; Travel, Angélique; Jondreville, Catherine; Maleix, Corentin; Baéza, Elisabeth; Engel, Erwan; Guérin, Thierry
Abstract: This study assessed the transfer of fumonisins B1 and B2 (FBs), zearalenone (ZEA) and zearalenone metabolites α-zearalanol (α-ZAL) and α-zearalenol (α-ZEL) to poultry tissues. Two experimental groups of 9 male chickens each were exposed for 8 weeks to a contaminated diet (FB group: 12.7 mg FB1 + FB2 kg −1, ZEA group: 0.40 mg ZEA kg −1 ). To measure the carry-over from feed to animal tissues (liver and muscle), a sensitive and accurate SIDA-UHPLC-MS/MS method was developed and validated. For all mycotoxins, the limit of detection (LOD) was 0.3 μg kg −1 and the limit of quantification (LOQ) was 1.0 μg kg −1 . Recoveries ranged from 92% to 107% and the intermediate precision coefficients of variation (CVIP ) were between 4.3% and 13%. ZEA and α-ZAL were not detected in livers, whereas α-ZEL was detected in five out of eight samples at levels between LOD and LOQ. FBs were detected and quantified in the livers of all animals exposed to the contaminated diet (mean 30.3 μg FB1 kg −1 and 2.3 μg FB2 kg −1 ). A significant correlation between the FB1 and the FB2 contents in the liver was demonstrated and FB carry-over factors (CFs) from feed to liver were determined (CFFB1 : 0.003 and CFFB2 : 0.001). Filet muscles from the same animals were also analysed. FB1 was quantified at trace levels in eight samples out of nine (mean 2.0 μg kg −1 ) and was only detected in the remaining sample. FB2 was detected in only one muscle sample. Highlights: Transfer assessment of fumonisins, zearalenone and its metabolites to poultry tissues. Full in-house validation of a sensitive SIDA-UHPLC-MS/MS method. A significant correlation between FB1 and FB2 contents in the liver was demonstrated. FB carry-over factors (CFs) from feed to liver were determined (FB1 0.003; FB2 0.001).